Developing building handover checklist for condominium buyers : case study of Kuala Lumpur / Lim Swee Meng - Lim, Swee Meng (2014)
In the new millennium century, a lot of property developments are being extended throughout the Malaysia territory. Purchasers of properties encounter numerous problems whenever vacant possession is delivered to them by developers. Besides that, public want to know whether have other building quality assessment as a guideline for them to inspect the properties. The aim of this dissertation is to produce a procedure and a guideline or checklist for the condominium purchaser. Besides that, this dissertation would access building construction quality on the vacant possession during the handover and post-handover process. The research is limited to residential buildings which are condominiums in the range between twenty five stories height to thirty five stories height. It was within the scope of the existing buildings in Malaysia (Kuala Lumpur) which is in the process of handing over to the purchasers. The study cases are carried out through visualization and with technical instruments (if need).